NMR Structure and Dynamics of TonB Investigated by Scar-Less Segmental Isotopic Labeling Using a Salt-Inducible Split Intein - Ciragan, Annika; Backlund, Sofia M.; Mikula, Kornelia M.; Beyer, Hannes M.; Samuli Ollila, O. H.; Iwaï, Hideo (Frontiers in Chemistry, 2020)
The growing understanding of partially unfolded proteins increasingly points to their biological relevance in allosteric regulation, complex formation, and protein design. However, structural characterization of disordered proteins remains challenging. NMR methods can access both the dynamics and structures of such proteins, yet they suffer from a high degeneracy of NMR signals. Here, we overcame this bottleneck utilizing a salt-inducible split intein to produce segmentally labeled samples with the native sequence, including the ligation junction. With this technique, we investigated the NMR structure and conformational dynamics of TonB from Helicobacter pylori in the presence of a proline-rich low complexity region. Spin relaxation experiments suggest that the several nano-second time scale dynamics of the C-terminal domain (CTD) is almost independent of the faster pico-to-nanosecond dynamics of the low complexity central domain (LCCD). Our results demonstrate the utility of segmental isotopic labelling for proteins with heterogenous dynamics such as TonB and could advance NMR studies of other partially unfolded proteins.